Beyond Legal Moralism: Reconstructing Rational Justice through Economic Analysis of Law in Indonesia’s Criminal Policy - Lesmana, CSA Teddy; Sulistiani, Lies; Putri, Nella Sumika; de Bats, August Peter (Jambe Law Journal, 2025)
This article critically interrogates the enduring dominance of the legal – moralistic paradigm in Indonesia’s legal system and advances the Economic Analysis of Law (EAL) as a rational and context – sensitive framework for legal reform. Departing from the premise that moralistic legal reasoning, when detached from empirical evaluation and incentive structures, often produces overcriminalization, regulatory inefficiency, and declining public trust, this study argues that EAL offers a systematic methodology to realign law with rational justice. Employing a multidisciplinary approach that integrates philosophical reflection, socio – legal analysis, and doctrinal examination, the article demonstrates that EAL is not antithetical to Indonesia’s constitutional identity or normative foundations, including Pancasila, but can instead function as an instrumental extension of its substantive justice values. By incorporating cost – benefit analysis, behavioral incentives, and evidence – based policy evaluation into legal decision – making, EAL enhances legislative rationality, optimizes enforcement mechanisms, and strengthens institutional legitimacy. Comparative insights drawn from selected jurisdictions, particularly the United Kingdom, Australia, South Korea, and Canada, illustrate how EAL has been institutionalized through Regulatory Impact Assessments, restorative justice frameworks, and interdisciplinary legal education. The article concludes by proposing a contextualized reform strategy for integrating EAL into Indonesia’s pluralistic legal culture, positioning rational justice as a mediating paradigm between moral aspiration, empirical governance, and democratic accountability.